2021
DOI: 10.1007/s40979-021-00075-9
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the COVID-19 emergency: student and academic staff perceptions of academic integrity in the transition to online exams at three Australian universities

Abstract: This paper explores the perceptions of academic staff and students to student cheating behaviours in online exams and other online assessment formats. The research took place at three Australian universities in July and August 2020 during the emergency transition to online learning and assessment in response to the COVID-19 pandemic. The study sought to inform decision making about the future of online exams at the participating universities. Quantitative and qualitative data were collected using online survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
86
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 45 publications
9
86
0
8
Order By: Relevance
“…as well as the extant literature on the topic. An examination of the current literature related explicitly to the COVID-19 and online assessments (Bilen & Matros 2020;Eaton 2020;Elzainy, El Sadik & Al Abdulmonem 2020;Gamage et al 2020;Jose 2021;Ng 2021;Reedy et al 2021) points to a dearth of engagement in the South African context (Ngqondi, Maoneke & Mauwa 2021). In order to address this particular deficiency, data were collected from an institutional forum on academic dishonesty at a University in South Africa in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…as well as the extant literature on the topic. An examination of the current literature related explicitly to the COVID-19 and online assessments (Bilen & Matros 2020;Eaton 2020;Elzainy, El Sadik & Al Abdulmonem 2020;Gamage et al 2020;Jose 2021;Ng 2021;Reedy et al 2021) points to a dearth of engagement in the South African context (Ngqondi, Maoneke & Mauwa 2021). In order to address this particular deficiency, data were collected from an institutional forum on academic dishonesty at a University in South Africa in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…The transition to online teaching and learning due to unforeseen circumstances has led to attempts to translate traditional examination formats used in lecture halls and other F2F environments to an online format. Because classroom testing was not possible, and invigilated assessments were not an option, safeguarding academic integrity became a challenge (Gamage et al, 2020;Reedy et al, 2021). In addition, many so-called "study aid" tutoring sites such as Chegg and Course Hero have emerged during the pandemic to help students with their take-home exams (Lancaster & Cotarlan, 2021).…”
Section: Academic Integrity and Assessment Design In Online Learningmentioning
confidence: 99%
“…However, as ERT has forced all students online, such a difference was no longer valid, and may be part of the explanation of why ERT has entailed such a sharp increase in misconduct cases in Sweden. A recent study in Australia has shown that younger students assumed that cheating was easier in an ERT online setting (Reedy et al, 2021). In addition, the ERT has forced students and teachers into an online environment without training and experience in such settings, and in some cases, as Eaton points out, against their will, which might also have affected academic integrity (Eaton, 2020).…”
Section: Academic Integrity and Assessment Design In Online Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Universities managed to continue their courses with the help of distance learning technologies (Huang et al, 2020, Grande-de-Prado et al, 2021. With the exception of subjects requiring laboratory or other special equipment (these subjects were moved to later semesters), almost every lesson was eventually moved online (Alessio & Messinger, 2021, Johnson et al, 2021, Chung et al, 2020, Graham, 2019, Reedy et al, 2021.…”
Section: Introductionmentioning
confidence: 99%